Can anyone give me some hints on how to prove $p\land q \rightarrow r \vdash (p \rightarrow r) \lor (q \rightarrow r)$ with natural deduction? I have spend hours trying to prove it to no avail. I know that double negation, negation rules are necessary here, however I kept get stuck and redoing it all over again many times.

Any kind of hints would be greatly appreciated, thank you.


1 Answer 1


Since double negation is needed a good aproach is to assume the negation of the conclusion as your first step, and then try to derivate a contradiction so that way you use $I¬$ and after that you use $E¬¬$. Try with this assumtions:

$1). (p ∧ q) ⇒ r - premise$

$2). ¬((p ⇒ r) ∨ (q ⇒ r)) - assumption$

$3). p - assumption$

$4). q - assumption$


  • 1
    $\begingroup$ I have actually solved the question, thank you for your insight. $\endgroup$
    – Liu YW
    Oct 5, 2020 at 2:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.